Finite Element Vibration Analysis of Beams, Plates and Shells - Jaroslav Mackerle (Shock and Vibration)
This bibliography lists references to papers, conference proceedings and theses/dissertations dealing with finite element vibration analysis of beams, plates and shells that were published in 1994–1998. It contains 361 citations. Also included, as separated subsections, are vibration analysis of composite materials and vibration analysis of structural elements with cracks/contacts.